Pendampingan Peningkatan Literasi bagi Generasi Muda di Desa melalui Program "SUDUT PINTAR" di Desa Tanjung Baru Ranau Kabupaten OKU Selatan: Assistance in Improving Literacy for the Youth in the Village through the "SUDUT PINTAR" Program in Tanjung Baru Ranau Village South OKU Regency - Martina, Martina; Austin, Trecy; Rafinzar, Rahmat; Munawir, Irsad; Chairani, Annisa Larasati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Reading interest and literacy levels in rural communities remain a serious challenge, including in Tanjung Baru Ranau Village, South OKU. The lack of reading materials, low family awareness of reading culture, and limited public learning spaces result in young people having limited access to knowledge sources. The main topic of this article is the effort to improve literacy among the younger generation in Tanjung Baru Ranau Village, South OKU Regency, through the Smart Corner Program. Discuss how low reading interest, limited reading facilities, and the scarcity of public learning spaces in villages are addressed through the establishment of open reading spaces (Smart Corners) equipped with diverse reading materials, literacy training, mentoring, and digital literacy strengthening. The implementation methods include socialization, literacy training, mentoring, and the application of technology and innovation through the provision of bookshelves, reading materials, floor mats, and reading tables. The results of the activity show an increase in understanding of digital literacy and reading interest among the younger generation, supported by the community’s high enthusiasm for managing the Smart Corner. Post-test evaluation showed significant improvement in understanding digital literacy, distinguishing between true and false information, and support for program sustainability. This program successfully strengthened the village literacy ecosystem and encouraged community participation in developing a reading culture. With youth and families involved, the Smart Corner has the potential to become a sustainable learning space that supports the achievement of SDGs 4 and 10.